A method for preparing high-purity low-chlorine copper powder using copper chloride etching waste liquid as raw material

Through reducing precipitation, washing, water ammonia dissolution, replacement and multiple reduction methods, the chloride ions and oxygen content in aluminum-substituted copper powder was successfully reduced, and the problem of high chloride ions content in copper powder in the prior art was solved, and the Preparation of copper powder with high purity, low chlorine and high dispersion.

CN118720157BActive Publication Date: 2025-02-21JIANGSU ZHIWEI NEW MATERIAL TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411225986.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-03
Publication Date
2025-02-21
Estimated Expiration
2044-09-03

AI Technical Summary

Technical Problem

The prior art is difficult to effectively reduce the chloride ion content and oxygen content, resulting in high chloride ion content in aluminum-substituted copper powder, which cannot meet the strict requirements of high-end ceramics for low-chloro copper powder.

Method used

Cutane chloride precipitation was obtained by reducing precipitation, and impurities were removed by sulfuric acid washing and hot water washing, water was added to dissolve and the impurities were removed by replacement of copper powder. Finally, hydrazine hydrate and secondary hydrogen reduction were carried out to reduce chloride ions and oxygen in copper powder. content.

Benefits of technology

The preparation of copper powder with high purity, low chlorine and high dispersion is achieved, which reduces the chloride ion and oxygen content in the copper powder, meets the requirements of high-end ceramics for low chlorine copper powder, and improves the stability and dispersion of copper powder. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118720157B_ABST
    Figure CN118720157B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing high-purity low-chlorine copper powder by using cupric chloride etching waste liquid as raw material, wherein the acidic cupric chloride etching waste liquid is filtered by a filter, sodium sulfite is added to the obtained filtrate, and cuprous chloride precipitation is obtained after stirring; the cuprous chloride precipitation is washed by adding sulfuric acid, and then pure water is added for washing, and after washing, hot water is added for washing, concentrated ammonia water is added to the obtained filter residue, and the obtained filter residue is stirred and dissolved, copper powder is added to the obtained filtrate, and the obtained filtrate is stirred for reaction and filtered, hydrazine hydrate is added to the obtained filtrate for reaction, and the obtained filter residue is washed and dried in a nitrogen oven; the dried material is placed in a reduction furnace, hydrogen is introduced for reduction, and then after cooling, the material is crushed under a nitrogen gas flow, and then vacuum-packed to obtain high-purity low-chlorine copper powder. The method for preparing high-purity low-chlorine copper powder by using cupric chloride etching waste liquid as raw material can obtain high-purity copper powder with low chlorine and oxygen, low bulk density and high stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing high-purity low-chlorine copper powder by taking copper chloride etching waste liquid as raw material, and belongs to the technical field of copper extraction. Background Art

[0002] Chemical etching is an important process in the manufacture of PCBs. It is one of the most complex chemical processes besides electroplating. This is because there are many different variables in the etching process that affect production efficiency and products. Although etching is complicated, the most common etching solutions commonly used by PCB manufacturers are acidic cupric chloride etching solutions and alkaline cupric chloride etching solutions (hereinafter referred to as acidic etching solutions and alkaline etching solutions), the latter of which is often referred to as "ammonia-containing alkaline etching solutions". Of course, there are other etching solutions, such as ferric chloride, sodium persulfate, and alkaline ammonium sulfate, but these etching solutions are not commonly used in the PCB manufacturing process. After processing the PCB, waste etching solution will be obtained, which contains acid, copper and other substances. If discharged, it will pollute the environment.

[0003] One of the disposal processes for waste acidic cupric chloride etching solution is to add aluminum sheets to replace it to obtain copper powder and aluminum chloride. The purity of aluminum-substituted copper powder is higher than that of iron-substituted copper powder, and the heavy metal impurities are low. It can be used to produce inorganic salts such as copper oxide and cuprous oxide. However, with the development of high-end ceramics, the requirements for chloride ions in aluminum-substituted copper powder are becoming more and more stringent. The chloride ion requirement is ≤100ppm, while the chloride ion content of aluminum-substituted copper powder is generally 1000-1500ppm. Common methods such as water rinsing or soap water soaking cannot reduce the chloride ion to below 800ppm. The main reason is that the chloride ion in the copper powder exists in the form of polyaluminum chloride, which is hydrolyzed and precipitated after water rinsing, and it is difficult to further reduce it.

[0004] Therefore, how to adopt waste acid cupric chloride etching solution to prepare low-chlorine copper powder has become one of the difficult problems in processing waste acid cupric chloride etching solution. Summary of the invention

[0005] In view of this, the present invention provides a method for preparing high-purity low-chlorine copper powder by taking cupric chloride etching waste liquid as raw material, wherein cuprous chloride precipitate is obtained by reduction precipitation, then washed with sulfuric acid to wash away some hydroxide precipitates of metal ions caused by the increase of pH value due to the addition of sodium sulfite, then washed with hot water to wash away part of the precipitated lead tetrachloride, then added with ammonia water for dissolution, the cuprous chloride can be dissolved by the ammonia water, while part of impurities cannot be dissolved by the ammonia water, then replaced by copper powder to replace a small amount of inert metal ion impurities, then obtain a pure copper-containing solution, after being reduced by hydrazine hydrate, secondary hydrogen reduction is performed, that is, the chloride ion content in the copper powder can be effectively reduced, and the oxygen content in the copper powder can be reduced, so as to obtain high-purity copper powder, and at the same time, the copper powder has low bulk density and high stability.

[0006] The present invention solves the above technical problems by the following technical means:

[0007] A method for preparing high-purity low-chlorine copper powder using copper chloride etching waste liquid as raw material of the present invention comprises the following steps:

[0008] (1) filtering the acidic copper chloride etching waste liquid through a filter, adding sodium sulfite to the obtained filtrate, and stirring to obtain a precipitate of cuprous chloride;

[0009] (2) After the cuprous chloride precipitate is washed with sulfuric acid, it is then washed with pure water. After washing, hot water is added, stirred for 30-60 minutes, and then filtered and washed. Concentrated ammonia water is added to the obtained filter residue, stirred to dissolve, copper powder is added to the obtained filtrate, stirred for reaction, and then filtered. Hydrazine hydrate is added to the obtained filtrate, and the reaction is carried out at a temperature of 50-80°C for 1-2 hours. The obtained filter residue is washed and then dried in a nitrogen oven;

[0010] (3) The dried material is placed in a reduction furnace, hydrogen is introduced for reduction, and then after cooling, it is crushed under a nitrogen flow and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0011] In the step (1), the filter is a ceramic membrane filter, the pore size of the ceramic membrane is 20-50 nm, and the solid suspended matter in the filtrate after filtration is less than 50 ppm; the molar number of the added sodium sulfite is 1:2.5-4 of the copper ions in the acidic copper chloride etching waste liquid, the time for adding sodium sulfite is 30-60 minutes, and the stirring reaction is continued for 30-60 minutes after the addition.

[0012] In the step (2), the concentration of the sulfuric acid solution is 0.5-1 mol / L, the mass ratio of cuprous chloride to sulfuric acid solution is 1:3-5, the temperature of the sulfuric acid solution during washing is 40-60°C, the washing soaking time is 30-60 min, after sulfuric acid washing, filtering, the obtained filter residue is washed with pure water at a temperature of 30-50°C, and the washing is stopped after washing until the conductivity of the washing water is ≤100 μS / cm, and then hot pure water of 80-100°C is added for washing, and after washing, filtering is performed, and then pure water is added again for washing until the conductivity of the washing water is ≤60 μS / cm, and then the washing is stopped, and the obtained filter residue is added with concentrated ammonia water at a concentration of 5-10 mol / L and a temperature of 30-50°C, stirred and dissolved for 30-60 min, and copper powder is added to the filtrate obtained by filtration, and the mass of the copper powder added is 0.05-0.1 times the mass of the filtrate, and the reaction is stirred at a temperature of 30-50°C for 30-60 min.

[0013] In the step (2), during the reduction process of adding hydrazine hydrate, the ratio of the molar number of hydrazine hydrate added to the molar number of copper ions in the purified filtrate is 1:2-3, the reduced filter residue is washed with pure water until the conductivity of the washing water is ≤60μS / cm, and then the washing is stopped. When the washed once reduced copper powder is dried in a nitrogen oven, the drying temperature is 80-100°C, the oxygen volume concentration in the oven during the drying process is ≤10ppm, and the drying is stopped after the free moisture of the material is ≤500ppm.

[0014] In the step (3), during the reduction process in the reduction furnace, the temperature is increased at a rate of 2-3°C / h to 300-400°C, and the reduction is carried out at this temperature for 2-4h, and then the material is cooled to a temperature of ≤60°C before being discharged, and then transported to a pulverizer by a nitrogen gas flow, pulverized by a nitrogen gas flow at a pressure of 5-8kg, and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0015] The present invention is aimed at the complex composition of acid copper chloride etching waste liquid, high metal impurity content, high acidity, high chloride ion and other characteristics, and proposes to reduce copper ions first, thereby obtaining cuprous chloride precipitation, because most of the chloride ions are soluble salts, and this step can be used to intercept most of the impurities, and then the cuprous chloride precipitation is acid-washed, and part of the hydroxide precipitation is washed away, such as iron ions, aluminum ions, chromium ions, tin ions, etc., and then the lead tetrachloride precipitation can be dissolved by hot water washing, and the purity of copper is further improved. The precipitation after hot water washing is dissolved by ammonia water, and cuprous chloride is dissolved, and some impurities insoluble in ammonia water are intercepted again, including iron ions, tin ions, lead ions, etc., and then the inert metal ions in the ammonia solution are replaced by copper powder, including mercury ions, silver ions, etc., and in the replacement liquid after the final replacement, the content of metal ion impurities such as iron, cobalt, nickel, zinc, silver, lead, tin, etc. is less than 5ppm.

[0016] A relatively pure copper solution is reduced to copper powder by hydrazine hydrate reduction. Because it is a low-temperature liquid phase reduction, the obtained copper powder has a high dispersibility. However, because it is a low-temperature liquid phase reduction and the reduction process occurs in an alkaline environment, the oxygen content and chlorine content in the copper powder are relatively high.

[0017] The present invention introduces secondary hydrogen reduction, which can effectively reduce the chloride ion content and oxygen content in the copper powder, so that the copper powder has higher purity and better dispersibility. In the second reduction process of the present invention, hydrogen reduction is adopted, and the residual chloride ions can be volatilized in the form of hydrogen chloride. In the second reduction process of the present invention, the reduction temperature is low and the reduction time is short, so that the melting of the copper powder at high temperature is avoided, and the morphology and dispersibility of the low-temperature liquid phase reduction process are inherited.

[0018] Through this process, using acid copper chloride etching waste liquid as raw material, high-purity, low-oxygen, low-chlorine, and highly dispersible copper powder can be obtained.

[0019] Beneficial effects of the present invention:

[0020] 1. The present invention aims at the characteristics of cupric chloride etching waste liquid, i.e., high metal impurity content, high acidity, high chloride ion and the like, and develops a new copper impurity removal method with high impurity removal efficiency, low copper loss rate, low impurity content and simple process flow.

[0021] 2. The present invention adopts a two-step reduction method, namely, low-temperature liquid phase reduction first and high-temperature hydrogen reduction, so that highly dispersible copper powder can be obtained, and its chloride ion and oxygen content can be reduced, thereby reducing its activity. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Attached Figure 1 This is the SEM of the product of Example 1.

[0023] Attached Figure 2 This is the SEM of the product of Example 2.

[0024] Attached Figure 3 This is the SEM of the product of Example 3. DETAILED DESCRIPTION

[0025] The present invention will be described in detail below in conjunction with specific embodiments and drawings. A method for preparing high-purity low-chlorine copper powder using copper chloride etching waste liquid as a raw material in the present embodiment comprises the following steps:

[0026] (1) filtering the acidic copper chloride etching waste liquid through a filter, adding sodium sulfite to the obtained filtrate, and stirring to obtain a precipitate of cuprous chloride;

[0027] (2) After the cuprous chloride precipitate is washed with sulfuric acid, it is then washed with pure water. After washing, hot water is added, stirred for 30-60 minutes, and then filtered and washed. Concentrated ammonia water is added to the obtained filter residue, stirred to dissolve, copper powder is added to the obtained filtrate, stirred for reaction, and then filtered. Hydrazine hydrate is added to the obtained filtrate, and the reaction is carried out at a temperature of 50-80°C for 1-2 hours. The obtained filter residue is washed and then dried in a nitrogen oven;

[0028] (3) The dried material is placed in a reduction furnace, hydrogen is introduced for reduction, and then after cooling, it is crushed under a nitrogen flow and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0029] In the step (1), the filter is a ceramic membrane filter, the pore size of the ceramic membrane is 20-50 nm, and the solid suspended matter in the filtrate after filtration is less than 50 ppm; the molar number of the added sodium sulfite is 1:2.5-4 of the copper ions in the acidic copper chloride etching waste liquid, the time for adding sodium sulfite is 30-60 minutes, and the stirring reaction is continued for 30-60 minutes after the addition.

[0030] In the step (2), the concentration of the sulfuric acid solution is 0.5-1 mol / L, the mass ratio of cuprous chloride to sulfuric acid solution is 1:3-5, the temperature of the sulfuric acid solution during washing is 40-60°C, the washing soaking time is 30-60 min, after sulfuric acid washing, filtering, the obtained filter residue is washed with pure water at a temperature of 30-50°C, and the washing is stopped after washing until the conductivity of the washing water is ≤100 μS / cm, and then hot pure water of 80-100°C is added for washing, and after washing, filtering is performed, and then pure water is added again for washing until the conductivity of the washing water is ≤60 μS / cm, and then the washing is stopped, and the obtained filter residue is added with concentrated ammonia water at a concentration of 5-10 mol / L and a temperature of 30-50°C, stirred and dissolved for 30-60 min, and copper powder is added to the filtrate obtained by filtration, and the mass of the copper powder added is 0.05-0.1 times the mass of the filtrate, and the reaction is stirred at a temperature of 30-50°C for 30-60 min.

[0031] In the step (2), during the reduction process of adding hydrazine hydrate, the ratio of the molar number of hydrazine hydrate added to the molar number of copper ions in the purified filtrate is 1:2-3, the reduced filter residue is washed with pure water until the conductivity of the washing water is ≤60μS / cm, and then the washing is stopped. When the washed once reduced copper powder is dried in a nitrogen oven, the drying temperature is 80-100°C, the oxygen volume concentration in the oven during the drying process is ≤10ppm, and the drying is stopped after the free moisture of the material is ≤500ppm.

[0032] In the step (3), during the reduction process in the reduction furnace, the temperature is increased at a rate of 2-3°C / h to 300-400°C, and the reduction is carried out at this temperature for 2-4h, and then the material is cooled to a temperature of ≤60°C before being discharged, and then transported to a pulverizer by a nitrogen gas flow, pulverized by a nitrogen gas flow at a pressure of 5-8kg, and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0033] Embodiment 1: A method for preparing high-purity low-chlorine copper powder using copper chloride etching waste liquid as raw material, comprising the following steps:

[0034] (1) The acid copper chloride etching waste liquid is filtered by a filter, the filter is a ceramic membrane filter, the pore size of the ceramic membrane is 20nm, the solid suspended matter in the filtrate after filtration is 12.4ppm, the obtained filtrate is added with sodium sulfite, after stirring, the molar number of the added sodium sulfite is 1:3 of the copper ion in the acid copper chloride etching waste liquid, the time of adding sodium sulfite is 30min, after adding, the stirring reaction is continued for 60min to obtain the precipitation of cuprous chloride; the cuprous chloride is sampled and tested, and the results are as follows:

[0035]

[0036] (2) After the cuprous chloride precipitate is washed with sulfuric acid, pure water is added for washing. The concentration of the sulfuric acid solution is 0.5 mol / L. The mass ratio of cuprous chloride to sulfuric acid solution is 1:5. The temperature of the sulfuric acid solution during washing is 40°C. The washing soaking time is 60 min. After washing with sulfuric acid, the filter is filtered and the filter residue is washed with pure water at a temperature of 30°C. Washing is stopped when the conductivity of the washing water is ≤100 μS / cm. After washing, hot pure water at 90°C is added for washing. After stirring for 30 min, the filter is filtered and washed. Pure water is then added for washing until the conductivity of the washing water is ≤60 μS / cm. The filter residue is added with concentrated ammonia water at a concentration of 8 mol / L and a temperature of 40°C and stirred for 50 min to dissolve. The obtained filtrate was added with copper powder, the mass of the added copper powder was 0.08 times the mass of the filtrate, and the reaction was stirred at a temperature of 40°C for 50 minutes. After the reaction was stirred, hydrazine hydrate was added to the obtained filtrate, and the reaction was carried out at a temperature of 80°C for 1 hour. During the reduction process of adding hydrazine hydrate, the ratio of the molar number of hydrazine hydrate added to the molar number of copper ions in the purified filtrate was 1:2.5. The reduced filter residue was washed with pure water until the conductivity of the washing water was ≤60μS / cm, and then the washing was stopped. When the washed once reduced copper powder was dried in a nitrogen oven, the drying temperature was 90°C, the oxygen volume concentration in the oven during the drying process was ≤10ppm, and the drying was stopped after the free moisture of the material was ≤500ppm. The once reduced copper powder was obtained, and the test data were as follows:

[0037]

[0038] (3) The dried material is placed in a reduction furnace and hydrogen is introduced for reduction. During the reduction process in the reduction furnace, the temperature is increased at a rate of 2.5°C / h to 350°C, and the material is reduced at this temperature for 3h. The material is then cooled to a temperature of ≤60°C before being discharged. The material is then transported to a pulverizer through a nitrogen gas flow, pulverized using a nitrogen gas flow at a pressure of 7kg, and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0039] The data of the copper powder finally detected are as follows:

[0040]

[0041] As attached Figure 1 As shown, the copper powder obtained in this example has a relatively smooth surface, a moderate BET, a spherical shape, and a primary particle size of about 200 nm.

[0042] From the above physical and chemical test data, the purity reaches 99.99%, the oxygen content is extremely low, the chloride ion content is less than 10ppm, and the bulk density and tap density are relatively large. It can be seen that the preparation of high-purity and low-chloride ion copper powder can be achieved through this technology. The content of other impurities is basically less than 10ppm.

[0043] Embodiment 2: A method for preparing high-purity low-chlorine copper powder using copper chloride etching waste liquid as raw material, comprising the following steps:

[0044] (1) filtering the acidic copper chloride etching waste liquid through a filter, adding sodium sulfite to the obtained filtrate, and stirring to obtain a precipitate of cuprous chloride;

[0045] (2) After the cuprous chloride precipitate is washed with sulfuric acid, it is then washed with pure water. After washing, hot water is added, stirred for 30 minutes, and then filtered and washed. Concentrated ammonia water is added to the obtained residue, stirred to dissolve, copper powder is added to the obtained filtrate, stirred for reaction, and then filtered. Hydrazine hydrate is added to the obtained filtrate, and the reaction is carried out at a temperature of 50°C for 2 hours. After washing, the obtained residue is dried in a nitrogen oven;

[0046] (3) The dried material is placed in a reduction furnace, hydrogen is introduced for reduction, and then after cooling, it is crushed under a nitrogen flow and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0047] In the step (1), the filter is a ceramic membrane filter, the pore size of the ceramic membrane is 20 nm, and the solid suspended matter in the filtrate after filtration is 10.5 ppm; the molar number of the added sodium sulfite is 1:2.5 of the copper ions in the acidic copper chloride etching waste liquid, the time for adding sodium sulfite is 60 minutes, and the stirring reaction is continued for 60 minutes after the addition.

[0048] In the step (2), the concentration of the sulfuric acid solution is 1 mol / L, the mass ratio of cuprous chloride to sulfuric acid solution is 1:3, the temperature of the sulfuric acid solution during washing is 40°C, the washing soaking time is 60 min, after sulfuric acid washing, filtering, the obtained filter residue is washed with pure water at a temperature of 30°C, and the washing is stopped after washing until the conductivity of the washing water is ≤100 μS / cm, and then 100°C hot pure water is added for washing, and then filtered, and then pure water is added again for washing until the conductivity of the washing water is ≤60 μS / cm, and then the washing is stopped, and the obtained filter residue is added with concentrated ammonia water at a concentration of 10 mol / L and a temperature of 30°C, stirred and dissolved for 30 min, and copper powder is added to the filtrate obtained by filtration, and the mass of the copper powder added is 0.05 times the mass of the filtrate, and the reaction is stirred at a temperature of 50°C for 30 min.

[0049] In the step (2), during the reduction process of adding hydrazine hydrate, the ratio of the molar number of hydrazine hydrate added to the molar number of copper ions in the purified filtrate is 1:2, the reduced filter residue is washed with pure water until the conductivity of the washing water is ≤60μS / cm, and then the washing is stopped. When the washed once reduced copper powder is dried in a nitrogen oven, the drying temperature is 80°C, the oxygen volume concentration in the oven during the drying process is ≤10ppm, and the drying is stopped after the free moisture of the material is ≤500ppm.

[0050] In the step (3), during the reduction process in the reduction furnace, the temperature is increased to 300°C at a heating rate of 2°C / h, and the temperature is reduced for 2h at this temperature. The material is then cooled to a temperature of ≤60°C before being discharged. The material is then transported to a pulverizer by a nitrogen gas flow, pulverized by a nitrogen gas flow at a pressure of 5kg, and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0051] The data of the copper powder finally detected are as follows:

[0052]

[0053] As attached Figure 2 As shown, the copper powder obtained in this example has a relatively smooth surface, a moderate BET, a spherical shape, and a primary particle size of about 200 nm.

[0054] Judging from the above physical and chemical test data, the purity reaches 99.992%. Through this technology, the preparation of high-purity, low-chloride ion copper powder can be achieved.

[0055] Embodiment 3: A method for preparing high-purity low-chlorine copper powder using copper chloride etching waste liquid as raw material, comprising the following steps:

[0056] (1) filtering the acidic copper chloride etching waste liquid through a filter, adding sodium sulfite to the obtained filtrate, and stirring to obtain a precipitate of cuprous chloride;

[0057] (2) After the cuprous chloride precipitate is washed with sulfuric acid, it is then washed with pure water. After washing, hot water is added, stirred for 60 minutes, and then filtered and washed. Concentrated ammonia water is added to the obtained residue, stirred and dissolved, copper powder is added to the obtained filtrate, stirred and reacted, and then filtered. Hydrazine hydrate is added to the obtained filtrate, and the reaction is carried out at a temperature of 80°C for 1 hour. After washing, the obtained residue is dried in a nitrogen oven;

[0058] (3) The dried material is placed in a reduction furnace, hydrogen is introduced for reduction, and then after cooling, it is crushed under a nitrogen flow and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0059] In the step (1), the filter is a ceramic membrane filter, the pore size of the ceramic membrane is 50 nm, and the filtrate after filtration has a solid suspended matter content of 20.1 ppm; the molar number of the added sodium sulfite is 1:4 of the copper ions in the acidic copper chloride etching waste liquid, the sodium sulfite is added for 60 minutes, and the stirring reaction is continued for 30 minutes after the addition.

[0060] In the step (2), the concentration of the sulfuric acid solution is 0.5 mol / L, the mass ratio of cuprous chloride to sulfuric acid solution is 1:5, the temperature of the sulfuric acid solution during washing is 60°C, the washing soaking time is 30 min, and after sulfuric acid washing, the filter is filtered, and the obtained filter residue is washed with pure water at a temperature of 50°C, and the washing is stopped after washing until the conductivity of the washing water is ≤100 μS / cm, and then hot pure water at 80°C is added for washing, and then pure water is added for washing until the conductivity of the washing water is ≤60 μS / cm, and then the washing is stopped. The obtained filter residue is added with concentrated ammonia water at a concentration of 5 mol / L and a temperature of 50°C, and stirred and dissolved for 60 min, and copper powder is added to the filtrate obtained by filtration, and the mass of the copper powder added is 0.1 times the mass of the filtrate, and the reaction is stirred at a temperature of 30°C for 30 min.

[0061] In the step (2), during the reduction process of adding hydrazine hydrate, the ratio of the molar number of hydrazine hydrate added to the molar number of copper ions in the purified filtrate is 1:3, the reduced filter residue is washed with pure water until the conductivity of the washing water is ≤60μS / cm, and then the washing is stopped. When the washed once reduced copper powder is dried in a nitrogen oven, the drying temperature is 80°C, the oxygen volume concentration in the oven during the drying process is ≤10ppm, and the drying is stopped after the free moisture of the material is ≤500ppm.

[0062] In the step (3), during the reduction process in the reduction furnace, the temperature is increased to 400°C at a heating rate of 3°C / h, and the temperature is reduced for 2h at this temperature. The material is then cooled to a temperature of ≤60°C before being discharged. The material is then transported to a pulverizer by a nitrogen gas flow, pulverized by a nitrogen gas flow at a pressure of 8kg, and then vacuum packaged to obtain high-purity low-chlorine copper powder.

[0063] The data of the copper powder finally detected are as follows:

[0064]

[0065] As attached Figure 3 As shown, the copper powder obtained in this example has a relatively smooth surface, a moderate BET, a spherical shape, and a primary particle size of about 220 nm.

[0066] Judging from the above physical and chemical test data, the purity reaches 99.991%. Through this technology, the preparation of high-purity, low-chloride ion copper powder can be achieved.

[0067] At the same time, through the two-step reduction of the present invention, the oxidation resistance of the copper powder is also greatly enhanced. The copper powder of Examples 1-3 and the high-purity copper powder purchased on the market (FSSS particle size is between 1-1.5 μm, hydrogen reduction process) are placed together in a normal temperature atmosphere, the temperature is 20±2°C, the humidity is 60±5%, and the oxygen content increase of the copper powder is finally measured. The results are as follows:

[0068]

[0069] From the above data, it can be seen that the copper powder obtained in Examples 1-3 has higher stability. When placed under the same environment for the same time, the increase in oxygen content is much less than that of conventional copper powder.

[0070] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the purpose and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A method for preparing low-chlorine copper powder using acidic copper chloride etching waste liquid as raw material, characterized in that: For the following steps: (1) filtering the acidic copper chloride etching waste liquid through a filter, adding sodium sulfite to the obtained filtrate, and stirring to obtain a precipitate of cuprous chloride; (2) After the cuprous chloride precipitate is washed with sulfuric acid, it is then washed with pure water. After washing, hot water is added, stirred for 30-60 minutes, and then filtered and washed. Concentrated ammonia water is added to the obtained filter residue, stirred to dissolve, copper powder is added to the obtained filtrate, stirred for reaction, and then filtered. Hydrazine hydrate is added to the obtained filtrate, and the reaction is carried out at a temperature of 50-80°C for 1-2 hours. The obtained filter residue is washed and then dried in a nitrogen oven; (3) placing the dried material into a reduction furnace, introducing hydrogen for reduction, cooling it, crushing it under a nitrogen flow, and then vacuum packaging it to obtain high-purity low-chlorine copper powder; In the step (1), the filter is a ceramic membrane filter, the pore size of the ceramic membrane is 20-50 nm, and the solid suspended matter in the filtrate after filtration is less than 50 ppm; the molar number of the added sodium sulfite is 1:2.5-4 of the copper ions in the acidic copper chloride etching waste liquid, the time for adding the sodium sulfite is 30-60 minutes, and the stirring reaction is continued for 30-60 minutes after the addition; In the step (2), the concentration of the sulfuric acid solution is 0.5-1 mol / L, the mass ratio of cuprous chloride to sulfuric acid solution is 1:3-5, the temperature of the sulfuric acid solution during washing is 40-60°C, the washing soaking time is 30-60 min, after sulfuric acid washing, filtering, the obtained filter residue is washed with pure water at a temperature of 30-50°C, and the washing is stopped after washing until the conductivity of the washing water is ≤100 μS / cm, and then hot pure water of 80-100°C is added for washing, and after washing, filtering, and then pure water is added again for washing until the conductivity of the washing water is ≤60 μS / cm, and then the washing is stopped, and the obtained filter residue is added with concentrated ammonia water with a concentration of 5-10 mol / L and a temperature of 30-50°C, stirred and dissolved for 30-60 min, and copper powder is added to the filtrate obtained by filtration, and the mass of the copper powder added is 0.05-0.1 times the mass of the filtrate, and the reaction is stirred at a temperature of 30-50°C for 30-60 min; In the step (2), during the reduction process of adding hydrazine hydrate, the ratio of the molar number of hydrazine hydrate added to the molar number of copper ions in the purified filtrate is 1:2-3, the reduced filter residue is washed with pure water until the conductivity of the washing water is ≤60μS / cm, and then the washing is stopped. When the washed primary reduced copper powder is dried in a nitrogen oven, the drying temperature is 80-100°C, the oxygen volume concentration in the oven during the drying process is ≤10ppm, and the drying is stopped after the free moisture of the material is ≤500ppm; In the step (3), during the reduction process in the reduction furnace, the temperature is raised to 300-400°C, the reduction is carried out at this temperature for 2-4 hours, the reduction is carried out at this temperature for 3-6 hours, and then the material is cooled to a temperature of ≤60°C before being discharged, and then transported to a pulverizer by a nitrogen gas flow, pulverized by a nitrogen gas flow at a pressure of 5-8kg, and then vacuum packaged to obtain high-purity low-chlorine copper powder.

Citation Information

Patent Citations

  • Method for manufacturing ultra-fine copper powder

    CN103878388A

  • Lead sulfide cadmium sediment treatment method

    CN108950220A

  • Anhydrous cuprous chloride production process

    CN109626411A